Endovascular treatment of renal artery stenosis in Germany: a retrospective analysis of the DEGIR registry 2018–2021 - Feyen, Ludger; Artzner, Christoph; Paprottka, Philipp; Haage, Patrick; Kröger, Knut; Alhmid, Bachar; Katoh, Marcus (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2023)
Purpose To provide an overview of endovascular treatment of renal artery stenosis (RAS) using the data of the Deutsche Gesellschaft für interventionelle Radiologie (DeGIR) quality management system.Materials and Methods A retrospective analysis was performed. Pre-, peri- and postprocedural data, technical success rates, complication rates, and clinical success rates at dismissal were examined.Results Between 2018 and 2021, 2134 angiography examinations of the renal arteries were performed: diagnostic angiography in 70 patients (3 %), balloon angioplasty in 795 (37 %), stent implantation in 1166 (55 %) and miscellaneous procedures in 103 (5 %). The lesion length was less than or equal to 5 mm in 1837 patients (87 %), between 5 and 10 mm in 197 (9 %), and between 10 and 20 mm in 62 (3 %). The degree of stenosis was less than 50 % in 156 patients (7 %), greater than 50 % in 239 (11 %), and greater than 70 % in 1472 (70 %). Occlusion was treated in 235 patients (11 %). Symptoms at discharge resolved in 600 patients (29 %), improved in 1012 (49 %), were unchanged in 77 (4 %), and worsened in 5 (0.2 %). Complications were reported in 51 patients (2.5 %) and the mortality rate was 0.15 %.Conclusion A substantial number of patients with RAS and occlusions were treated by radiologists in Germany, with high technical success rates and low complication rates. The indication should be determined carefully as the current European guidelines for the treatment of RAS suggest that only carefully selected groups of patients will benefit from recanalizing treatment.Key Points:
Keywords: renal arteries; quality management; renal angiography; stents; renal artery occlusion; interventional procedures